"I love weather more than anybody": A digital ethnography of The Weather Channel's fan community. (July 2020) - Shermak, Jeremy L; Whipple, Kelsey N
We Love Weather is the fan community of The Weather Channel. Launched in 2016, We Love Weather aims to serve so-called "weather geeks" by providing exclusive and specialized weather content, as well as participatory and communal elements. This study proposes that We Love Weather is an "affinity space" where participants create, procure, and develop content and knowledge. It exemplifies the power and capability of a high-functioning, efficient online information hub. Using digital ethnographic analysis of We Love Weather's discussion forums and user-generated content, we found that We Love Weather promotes teaching and learning of weather information through sharing and community maintenance that establishes the site as an affinity space. It is an example of a positive, helpful, and deliberative online space.